The relationship between transformational, transactional leadership style and organizational commitment in GLCs in Kuching, Sarawak : mediating role of followership dimensions - Joleen Vicky, Keron (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The objectives of conducting this research were to identify the relationship between leadership styles, followership dimensions, and organizational commitment. Besides, this study was also conducted to identify the mediating role of followership dimensions in the relationship between leadership styles and organizational commitment. The leadership styles included in this study are transformational leadership style and transactional leadership style while followership dimensions include active engagement and independent, critical thinking. Among the research needs that solidified the importance of carrying out this research were the need to gain deeper understanding on the subject of leadership and commitment among Malaysian workforce. This is due to the lack of past researches conducted on these subjects within Malaysia context. Besides, followership dimensions were included as a mediator to enhance the understanding on the underlying mechanism and processes in the relationship between leadership style and organizational commitment especially in Malaysia workforce. The research sample of this study were employees from the 33 branches of GLCs in Kuching that participated in this study. This study focused on the followers’ perception on the leadership style exhibited by their leaders, their self-assessed followership dimension, and organizational commitment. The data for this research was obtained through 402 completed questionnaires gathered from the research participants. The analysis conducted confirms that leadership styles correlates with organizational commitment as well as with followership dimensions. The analysis also confirms that followership dimensions correlates with organizational commitment. In regards to the mediating role of followership dimensions, the analysis found that followership dimensions does act as a mediator in the relationship between leadership styles and organizational search are with hope able to contribute to the understanding on the subject of leadership, followership, and organizational commitment in Malaysia.